SOCIAL AND HUMAN RIGHTS AND STATE FUNCTIONS TO PROVIDE THEM - Petroie O.M. (Pressing Problems of Public Administration, 2016)
The article was an attempt to theoretical and methodological analysis of the nature and content of social and human rights; it was found that current approaches in this sphere are based on a broad and narrower sense it; was proposed classi cation structure and was revealed the contents of the social and human rights as the basis for determining the functions of the state for their support.